Reproduksi Makna dan Fungsi Turistik Praktik Ritual Perang Ketupat di Desa Kapal, Badung - Sendra, I Made; Kristianto, Yohanes; Nugroho, Saptono (Jurnal Kajian Bali (Journal of Bali Studies); Vol 9 No 1 (2019): WACANA KRITIS BUDAYA BALIDO - 10.24843/JKB.2019.v09.i01.p09, 2019)
This article is aimed to reinterpret the ritual of Ketupat War based on practical consciousness into reflexive consciousness to preserve agricultural tradition in Kapal Village, Badung Regency. This consciousness could be created by deconstructing the pragmatic materialistic perspective by promoting local knowledge Tri Hita Karana, philosophy on the harmonious relationship among human being, human and nature, and God. This research applied a descriptive qualitative method and structuration approach from Giddens to explain the ritual Perang Ketupat as reflexive consciousness. The research shows that the local people at Kapal Village interpret this ritual as practical consciousness without knowing the function and the meaning of the ritual. It means that ritual is only performed annually as a routine tradition. Therefore, reflexive consciousness needs to be nurtured through constructing the community`s awareness of this ritual as a tourist attraction, so that they can get the economic benefit (touristic meanings). In other words, tourism becomes a melting-pot producing space of the triple sections among nature, culture and tourism which is called Eco-Cultural Tourism Landscape (ECTL).